PENGARUH MEDIA SPELLING GAME TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN INPRES 1 TANGGA - Anita Hayatunnufus; Mulyadi; Zulkifli; Ilyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low beginning reading ability of elementary school students, especially in spelling aspects, due to the lack of interactive and engaging learning media. This study aimed to determine the effect of the Spelling Game media on the beginning reading ability of second-grade elementary school students in spelling aspects. This study used a quantitative approach with a quasi-experimental method employing a nonequivalent control group design. The sample consisted of 20 students divided into an experimental group and a control group, with 10 students in each group. Data were collected through beginning reading ability tests using pretest and posttest instruments. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Independent Sample t-test with the assistance of Jamovi software. The results showed that the average posttest score of the experimental group was 81.8, which was higher than the control group score of 68.5. The hypothesis test obtained a significance value of 0.003 < 0.05, indicating that the use of Spelling Game media had a significant effect on students’ beginning reading ability in spelling aspects. Therefore, Spelling Game media can be used as an effective and interactive learning alternative to improve elementary school students’ beginning reading ability.